Effect of a prior intermittent run at vVO2max on oxygen kinetics during an all-out severe run in humans - Billat, V. L.; Bocquet, V.; Slawinski, J.; Laffite, L.; Demarle, A.; Chassaing, P.; Koralsztein, J. P. (The Journal of Sports Medicine and Physical Fitness, 2000)
BACKGROUND: The purpose of this study was to examine the influence of prior intermittent running at VO2max on oxygen kinetics during a continuous severe intensity run and the time spent at VO2max. METHODS: Eight long-distance runners performed three maximal tests on a synthetic track (400 m) whilst breathing through the COSMED K4 portable telemetric metabolic analyser: i) an incremental test which determined velocity at the lactate threshold (vLT), VO2max and velocity associated with VO2max (vVO2max), ii) a continuous severe intensity run at vLT+50% (vdelta50) of the difference between vLT and vVO2max (91.3+/-1.6% VO2max)preceded by a light continuous 20 minute run at 50% of vVO2max (light warm-up), iii) the same continuous severe intensity run at vdelta50 with a prior interval training exercise (hard warm-up) of repeated hard running bouts performed at 100% of vVO2max and light running at 50% of vVO2max (of 30 seconds each) performed until exhaustion (on average 19+/-5 min with 19+/-5 interval repetitions). This hard warm-up speeded the VO2 kinetics: the time constant was reduced by 45% (28+/-7 sec vs 51+/-37 sec) and the slow component of VO2 (deltaVO2 6-3 min) was deleted (-143+/-271 ml x min(-1) vs 291+/-153 ml x min(-1)). In conclusion, despite a significantly lower total run time at vdelta50 (6 min 19+/-0) min 17 vs 8 min 20+/-1 min 45, p=0.02) after the intermittent warm-up at VO2max, the time spent specifically at VO2max in the severe continuous run at vdelta50 was not significantly different.